2007
DOI: 10.1016/j.juro.2007.07.117
|View full text |Cite
|
Sign up to set email alerts
|

Third-Generation Nephrectomy by Natural Orifice Transluminal Endoscopic Surgery

Abstract: Purpose:Recently there has been increasing enthusiasm for performing simple abdominal procedures by transgastric surgery. We previously reported the usefulness of a combined transgastric and transvesical approach to cholecystectomy. In this study we assessed the feasibility of combined transgastric and transvesical approach for performing a more complex surgical procedure, such as nephrectomy, in a porcine model. Materials and Methods: In a nonsurvival study combined transgastric and transvesical approaches we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
64
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 117 publications
(65 citation statements)
references
References 23 publications
0
64
0
1
Order By: Relevance
“…In fact, after the description of the transvesical port and its usefulness to perform several intra-abdominal procedures (ie, cholecystectomy and nephrectomy), it would be advantageous to develop a reliable closure method for vesicotomy which avoids bladder catheterization [18,19]. We believe the observations presented here might be relevant to transluminal procedures performed during NOTES procedures using the transvesical approach.…”
Section: Discussionmentioning
confidence: 82%
“…In fact, after the description of the transvesical port and its usefulness to perform several intra-abdominal procedures (ie, cholecystectomy and nephrectomy), it would be advantageous to develop a reliable closure method for vesicotomy which avoids bladder catheterization [18,19]. We believe the observations presented here might be relevant to transluminal procedures performed during NOTES procedures using the transvesical approach.…”
Section: Discussionmentioning
confidence: 82%
“…Transvesical access to the abdominal cavity either alone or in combination with transgastric access has been used for a broad range of procedures such as peritoneoscopy, liver biopsy, lung biopsy, cholecystectomy, nephrectomy, and partial cystectomy [7][8][9][10][11][12]. More recently, Gettman et al [13] reported the clinical feasibility of transvesical peritoneoscopy by using a flexible ureteroscope (DUR-8) during a case of robotic radical prostatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Soon it became apparent that this access was not only a major shift in how the bladder was seen, but also a safe and fast means of access to the peritoneal cavity, with an excellent view of all the upper peritoneal structures [7]. This same group of researchers also described the execution of complex surgical procedures, including nephrectomy [8] and cholecystectomy [9,10], which were carried out by an approach combining the transvesical port with the transgastric port. In both surgical procedures, the transvesical port represented not only a working port through which many instruments are used, but also a way of support and guidance in choosing the site of entry into the peritoneal cavity via the transgastric port [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…These developments marked a new era in minimally invasive abdominal surgery, compelling novel, previously audacious goals, such as avoidance of incisions and pain. With the visceral wall no longer a barrier to endoscopic intervention, various authors described novel, complex abdominal procedures [6][7][8][9][10][11][12][13][14][15][16]. In 2006, such reports motivated researchers in this emerging field to organize the Natural Orifice Surgery Consortium for Assessment and Research (NOSCAR), a joint initiative supported by the American Society for Gastrointestinal Endoscopy (AGES) and the Society of American Gastrointestinal and Endoscopic Surgeons (SAGES).…”
Section: Introductionmentioning
confidence: 99%